Investigating the Public Sentiment in Major Public Emergencies Through the Complex Networks Method: A Case Study of COVID-19 Epidemic - Guang Yang; Zhidan Wang; Lin Chen (Frontiers Media S.A., 2022)
The main purpose of this study is to investigate what topic indicators correlate with public sentiment during "coronavirus disease 2019 (COVID-19) epidemic" and which indicators control the complex networks of the topic indicators. We obtained 68,098 Weibo, categorized them into 11 topic indicators, and grouped these indicators into three dimensions. Then, we constructed the complex networks model of Weibo's topics and examined the key indicators affecting the public's sentiment during the major public emergency. The results showed that "positive emotion" is positively correlated with "recordings of epidemic" and "foreign comparisons," while "negative emotion" is negatively correlated with "government image," "recordings of epidemic," and "asking for help online." In addition, the two vertexes of "recordings of epidemic" and "foreign comparisons" are the most important "bridges" which connect the government and the public. The "recordings of epidemic" is the main connection "hub" between the government and the media. In other words, the "recordings of epidemic" is the central topic indicator that controls the entire topic network. In conclusion, the government should publish the advance of the events through official media on time and transparent way and create a platform where everyone can speak directly to the government for advice and assistance during a major public emergency in the future.